Improving the oral bioavailability of buprenorphine: an in‐vivo proof of concept. (26th October 2016) - Joshi, Anand; Halquist, Matthew; Konsoula, Zacharoula; Liu, Yongzhen; Jones, J.P.; Heidbreder, Christian; Gerk, Phillip M.
Abstract: Objectives: The aim of this study was to improve the oral bioavailability of buprenorphine by inhibiting presystemic metabolism via the oral co‐administration of 'Generally Recognized as Safe' compounds, thus providing an orally administered drug product with less variability and comparable or higher exposure compared with the sublingual route. Methods: The present studies were performed in Sprague Dawley rats following either intravenous or oral administration of buprenorphine/naloxone and oral co‐administration of 'Generally Recognized as Safe' compounds referred to as 'adjuvants'. Plasma samples were collected up to 22 h postdosing followed by liquid chromatography coupled to tandem mass spectrometry (LC‐MS/MS) analysis. Key findings: The adjuvants increased C max (21 ± 16 ng/ml vs 75 ± 33 ng/ml; 3.6‐fold) and AUC(0–22 h) (10.6 ± 8.11 μg min/ml vs 22.9 ± 11.7 μg min/ml; 2.2‐fold) values of buprenorphine (control vs adjuvant‐treated, respectively). The absolute oral bioavailability of buprenorphine doubled (from 1.24% to 2.68%) in the presence of the adjuvants. Conclusions: One may suggest that the adjuvant treatment most likely inhibited the presystemic metabolic enzymes, thus decreasing the intestinal 'first‐pass effect' on buprenorphine. Additional studies are now required to further explore the concept of inhibiting presystemic metabolism of buprenorphine by adjuvants to potentially increase the oral bioavailability of buprenorphine.